2008
DOI: 10.1080/09638280701191826
|View full text |Cite
|
Sign up to set email alerts
|

Robotic gait trainer in water: Development of an underwater gait-training orthosis

Abstract: Using the RGTW could expect not only the effect of the hydrotherapy but also the standard treadmill gait training, in particular, and may be particularly effective for treating individuals with hip joint movement dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…The performance of SCG participants in water is mainly due to the physical properties of water, especially buoyancy and hydrostatic pressure, which act in a way that decreases apparent body weight and contributes to ascending movements (9,28). These properties lead to a reduced requirement for muscle activation (15) and for the generation of joint torque (18).…”
Section: Discussionmentioning
confidence: 99%
“…The performance of SCG participants in water is mainly due to the physical properties of water, especially buoyancy and hydrostatic pressure, which act in a way that decreases apparent body weight and contributes to ascending movements (9,28). These properties lead to a reduced requirement for muscle activation (15) and for the generation of joint torque (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the system involves compressed air and the expansion and contraction of the braided rubber tube, it is possible to perform the orthosis in an underwater rehabilitation training scenario. Our earlier laboratory study of the robotic gait trainer (RGTW) indicated that hydrotherapy may be particularly effective in the treatment of individuals with hip joint movement dysfunction [26]. Since the PMA characteristics are based on its model parameters such as dimension (i.e., length and contraction) and pressure, the maximum contraction of PMA will prevent the exoskeleton of the AIRGAIT leg orthosis from exceeding the limitation of the joints [27].…”
Section: Safety Featuresmentioning
confidence: 99%
“…However, the design philosophy of this system may provide a significant insight into the development of rehabilitation orthosis systems and improve rehabilitative procedures for paraplegic patients. [38]; and (c) powered ankle-foot exoskeleton [39].…”
Section: It Was Developed In 2006 As Shown Inmentioning
confidence: 99%